2009
DOI: 10.1037/a0015673
|View full text |Cite
|
Sign up to set email alerts
|

Using client feedback in psychotherapy training: An analysis of its influence on supervision and counselor self-efficacy.

Abstract: Tracking client outcome and the therapeutic relationship across treatment (i.e., client feedback) has become a recommended practice for clinicians. This study investigated whether the utility of this practice would extend to trainees if the data gained from clients was provided to their supervisor for use within supervision. Trainees (N ϭ 28) were assigned to a continuous feedback condition or no-feedback condition for 1 academic year. Results indicated that trainees in both conditions demonstrated better clie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
118
3
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(130 citation statements)
references
References 44 publications
4
118
3
2
Order By: Relevance
“…While prior research on the link between supervision and therapist self-efficacy had been mixed [21][22][23][24], the present study found very clear support for this relationship; this difference is perhaps attributable to the surveying of experienced Masters level clinicians in the present study as opposed to graduate student clinicians in prior work.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…While prior research on the link between supervision and therapist self-efficacy had been mixed [21][22][23][24], the present study found very clear support for this relationship; this difference is perhaps attributable to the surveying of experienced Masters level clinicians in the present study as opposed to graduate student clinicians in prior work.…”
Section: Discussioncontrasting
confidence: 47%
“…In university training clinics or laboratory settings with graduate student trainees, some studies have found an increase in self-efficacy related to participation in clinical supervision [21,22] while other studies have not found such an advantage [23,24]. The present study was aimed at shedding light on the link between participation in ongoing consultation and coaching and therapist self-efficacy in seasoned clinicians.…”
Section: Introductionmentioning
confidence: 91%
“…Reese et al (2009b) found that clients of those students receiving continuous feedback over the course of therapy demonstrated better treatment outcomes (as perceived by the client) than the clients of those students not receiving it. Additionally, the supervisors reflected that utilizing the feedback data during supervision made the process of delivering critical feedback easier and it allowed them an entry point for giving more specific feedback.…”
Section: Application Of Continuous Client Feedback In Counselor Educamentioning
confidence: 99%
“…During experiential coursework, counselors in training enter the clinical world for the first time as the primary provider of services and are in need of feedback (Bernard & Goodyear, 2013;Skovholt & Ronnestad, 2003;Worthen & Lambert, 2007). Reese et al (2009aReese et al ( , 2009b suggest that this feedback should come directly from clients. Data based evaluation of student progress or remediation is instrumental to enhancing student development; this is preferred over attempts to use inflated or inaccurate reassurances from self or supervisor that serve little educational or developmental ends (Holloway & Neufeldt, 1995).…”
Section: Integrating Continuous Client Feedback Into the Curriculummentioning
confidence: 99%
“…2009; Reese et al, 2009). Each of these studies yielded significantly different results, and despite stronger methodology than the reviews cited above, the extent to which supervision impacts client outcome is unclear.…”
mentioning
confidence: 99%